Efetivitas Peran Relawan Dalam Membangun Kesolidan Sebuah Organisasi - Imam Prawoto (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2022)
In an organization, it is necessary to have souls willing to sacrifice and fight for each individual member. These souls are the main pillars of the establishment of an organization. Individuals who have this spirit are called organizational volunteers. In this context, it can be seen how many motivational motives a person has to volunteer. The research method used is a qualitative method with an empirical normative approach. The results of the study stated that in building organizational solidity, the role of volunteers (volunteers) who are willing to fight and sacrifice for the interests of their organization is needed. While in Islam, volunteering will be worth a deed of worship and be a good thing for the perpetrator.Keywords: Volunteer; Organization; Solidarity Abstrak:Dalam sebuah organisasi diperlukan adanya jiwa-jiwa mau berkorban dan berjuang pada setiap individu anggotanya. Jiwa-jiwa inilah yang menjadi penopang utama berdirinya sebuah organisasi. Individu-individu yang memiliki jiwa seperti ini disebut sebagai relawan organisasi. Dalam konteks ini, terlihat berberapa motif motivasi seseorang menjadi sukarelawan. Metode Penelitian yang digunakan adalah metode kualitatif dengan pendekatan normative empiris. Hasil penelitian menyatakan bahwa dalam membangun kesolidan organisasi diperlukan peran relawan (volunteer) yang rela berjuang dan berkorban untuk kepentingan organisasinya. Sedang dalam Islam, menjadi sukarelawan akan bernilai amal ibadah dan menjadi kebaikan pada diri pelakunya.Kata Kunci: Relawan; Organisasi; Kesolidan